2007
DOI: 10.1128/jb.01270-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofHelicobacter pyloriLytic Transglycosylases Slt and MltD

Abstract: Peptidoglycan (PG) is a cell wall heteropolymer that is essential for cell integrity. PG hydrolases participate in correct assembly of the PG layer and have been shown to be required for cell division, cell daughter separation, and maintenance of bacterial morphology. In silico analysis of the Helicobacter pylori genome resulted in identification of three potential hydrolases, Slt, MltD, and AmiA. This study was aimed at determining the roles of the putative lytic transglycosylases, Slt and MltD, in H. pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 24 publications
6
45
2
Order By: Relevance
“…The functions of LtgB and LtgE remain a mystery (19), although mutation of ltgE has a slight effect on PG dimer release (Fig. 2), a result consistent with its possible role as an endolytic transglycosylase as predicted from H. pylori studies (2).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The functions of LtgB and LtgE remain a mystery (19), although mutation of ltgE has a slight effect on PG dimer release (Fig. 2), a result consistent with its possible role as an endolytic transglycosylase as predicted from H. pylori studies (2).…”
Section: Discussionsupporting
confidence: 62%
“…A putative lytic transglycosylase gene (ltgE) encoding a protein similar to E. coli MltD was identified in the gonococcal chromosome by sequence comparisons (Table 2). An analysis of H. pylori mutants deficient in the LtgE homologue (MltD) indicated that the H. pylori enzyme acts as an endo-type lytic transglycosylase, shortening chain length and increasing anhydro ends in intact cell walls (2). Such an activity might generate more substrates for exo-type lytic transglycosylases and increase anhydro PG monomer production.…”
Section: Resultsmentioning
confidence: 99%
“…10 In Helicobacter pylori the MltD homologue is thought to act as an endo-type LT. Also, an mltD mutant showed decreased autolysis in stationary-phase culture. 7 It is unknown whether the gonococcal ltgE mutant is affected in these processes.…”
Section: Lts Of Unknown Function: Ltgb and Ltgementioning
confidence: 99%
“…The insertion of a flagellum would require a localized rearrangement of the PG layer involving endo-activity rather than the processive release of 1,6-anhydroMurNAc products that accompany its turnover during biosynthesis. This type of functional specificity involving the rearrangement of the sacculus has been ascribed to H. pylori MltD (39).…”
Section: Discussionmentioning
confidence: 99%